Pemodelan Laju Perubahan Nilai Tukar Rupiah (IDR) terhadap Dolar Amerika (USD) dengan Metode Markov Switching Autoregressive (MSAR) - Yurinanda, Sherli; Putri, Darvi Mailisa (UIN Imam Bonjol Padang, 2021)
This study aims to determine the modeling of the exchange rate change rate of the Rupiah (IDR) against the US dollar (USD) using the Markov Switching Autoregressive (MSAR) method. The research data is sourced from secondary data through website investing to see the Rupiah exchange rate against the US dollar with a time span from January to December 2020. The results show that the best model obtained is MS(2)AR(3) with parametersÂ = 0.031119 and = -0.000504,Â where when state = 1, the average rate of change in the rupiah exchange rate against the US dollar is 0.031119 per day, while when state = 2 the average rate of change in the rupiah exchange rate against the US dollar is -0.000504 per day.Â